IMPACT OF COOPERATIVE SOCIETIES SAVINGS SCHEME IN RURAL FINANCE: SOME EVIDENCE FROM NIGERIA - Onafowokan O. Oluyombo (Economic Review)
This paper examines the extent to which savings products offered by cooperative societies in some parts of Nigeria meet the financial needs of the rural dwellers. The study used the data from interviews and focus group discussions from randomly selected members of cooperative societies in six local governments. The data are analzed using percentages, content analysis and quotation. The study found that the savings product helps to inculcate a good savings habit among the participants because they find it easier to save now than when they were introduced to the program. The members also developed self esteem as “part owners” of the program because of the compulsory savings that they participate in, and they do not want the program to collapse. Members are also satisfied because they are able to save in the scheme which helps them to reduce their expenses on frivolous spending such as leisure drinking and acquisition of more wives. The members’ inability to withdraw from their savings when in financial need, except on cessation of membership, was found as the drawback of the program.